First record of Rilipertus Haeselbarth (Hymenoptera: Braconidae: Euphorinae) from China with description of a new species - Li, Jun; Zheng, Min-Lin; Chen, Jia-Hua (Zootaxa, 2020)
Euphorinae (Hymenoptera, Braconidae) is a large subfamily of endoparasitoid wasps with 1,270+ described species worldwide (Yu et al. 2016). In the phylogenetic analysis of Stigenberg et al. (2015) Rilipertus Haeselbarth, 1996 was recovered within the tribe Perilitini Forster,1862 together with several other genera. Rilipertus is morphologically similar to Microctonus Wesmael, 1836 and Perilitus Nees, 1819 by the type of wing venation, structure of propodeum, and shape and structure of first metasomal tergite. However, Rilipertus differs distinctly from them by having shorter and conspicuously broadened ovipositor sheaths and the sculpture of the first tergite is reduced. Six species of Rilipertus are currently known (Yu et al. 2016).